Pengaruh Edukasi Gizi Media Video terkait Kekurangan Energi Kronis (KEK) terhadap Pengetahuan dan Sikap Remaja Putri: The Influence of Video Media Nutrition Education on Chronic Energy Deficiency (CED) on the Knowledge and Attitudes of Adolescent Girls - Isnaini, Rafa; Andi Mukramin Yusuf; Umami, Zakia; Irawan, Andi Muh Asrul; Rahmawati, Lusi Anindia (Svasta Harena: Jurnal Ilmiah Gizi, 2024)
Background: CED generally occurs in Women of Childbearing Age (WCA), especially adolescent girls who are in the preconception period. The prevalence of CED in WCA in the age range of 15-19 years is included in the high category, this is a problem because it will have an impact on children's health and nutrition problems in the future. Purpose: This study aims to analyze the effect of nutrition education related to CED on adolescent preconception through video media on the knowledge and attitudes of adolescent girls at SMAN 92 Jakarta. Methods: This study used a Quasi Experiment Two Group Pre-Post Test research design. This study was conducted in June 2024 with a sample of 74 people. Primary data were obtained from questionnaires from respondent interviews. The sampling technique used purposive sampling with data analysis using the Wilcoxon statistical test. Results: The results showed that there was an increase in knowledge score of 20,41 in the intervention group and 12,97 in the control group. Providing nutrition education using video media provides an increase in knowledge. And there was an increase in attitude scores of 6,79 in the intervention group and 7,48 in the control group. Providing nutrition education using video media provides changes in improving attitudes. Conclusion: Providing education using video media is more effective in improving the knowledge of adolescent girls when compared to Powerpoint. However, in the attitude category, both media, namely video and Powerpoint, are equally effective in changing the attitudes of adolescent girls. In the future, it is hoped that video media can be utilized properly as an alternative option for nutrition education media.